WADAH KOMUNITAS EDUTANI DI RAWA BUNGA - Pinky Hemnani; Diah Anggraini (Jurusan Arsitektur dan Perencanaan, 2020)
According to Rey Oldenburg in the book The Great Good Place (1997) regardless of the first place (residence / house) and second place (place of work), humans need a third place as a space to meet those needs. This need is increasing in line when the social life of the community develops from complex to multi-complex. Meanwhile, Jakarta, which is characterized by metropolitan cities in Indonesia, makes its population have a fast and instant lifestyle. The comprehension of the importance of healthy eating is one of the things that is forgotten. Unhealthy eating patterns cause urban problems with higher mortality rates at 45-50 years old. Therefore, this study aims to produce the concept of designing a third place which, in addition to being a forum for interaction, and education about healthy eating can also improve the economy through strengthening communities in urban agriculture for people in Rawa Bunga and surrounding areas. The design of the third place project uses the disprogramming method of Bernard Tchumi, by combining two different program configurations, namely: edutani program as part of a community program with a commercial program. This disprogramming method then becomes the foundation in composing time compositions, which results in building designs that can meet the characteristics of third place and open architecture; namely; playful, conversation, neutral, leveler, accessibility and accommodation, a low profile and regulars. Keywords: agriculture education; healthy eating; third placeAbstrakMenurut Rey Oldenburg dalam buku The Great Good Place (1997) terlepas dari first place (tempat tinggal/rumah) dan second place (tempat bekerja), manusia memerlukan third place (tempat ketiga) sebagai ruang untuk memenuhi kebutuhan tersebut. Kebutuhan ini meningkat sejalan dengan kehidupan sosial masyarakat berkembangan dari kompleks menjadi multi kompleks. Sementara itu, Jakarta yang bercirikan kota metropolitan di Indonesia membuat penduduknya memiliki gaya hidup yang serba cepat dan instan. Pemahaman masyarakat akan pentingnya pola makan sehat menjadi salah satu hal yang terlupakan. Pola makan yang tidak sehat menimbulkan permasalahan perkotaan dengan tingkat kematian yang semakin tahun semakin tinggi pada usia 45-50 tahun. Oleh karena itu, kajian ini bertujuan untuk menghasilkan konsep perancangan sebuah third place yang selain dapat menjadi wadah interaksi, dan edukasi tentang pola makan sehat juga dapat meningkatkan perekonomian melalui penguatan komunitas dalam pertanian perkotaan bagi masyarakat di kelurahan Rawa Bunga dan sekitarnya. Perancangan proyek third place ini menggunakan metode disprogramming dari Bernard Tchumi, dengan menggabungkan dua konfigurasi program yang berbeda yaitu: program edutani sebagai bagian dari program komunitas dengan program komersial. Metode disprogramming ini kemudian menjadi landasan dalam menyusun gubahan masa, yang menghasilkan rancangan bangunan yang dapat memenuhi karakter-karakter third place dan open architecture; yaitu playful, conversation, neutral, leveler, accessibility and accommodation, a low profile and regulars.